The impact of Date Palm Pollen Capsule on Vaginal Iubrication and Dyspareunia In Menopausal Woman - Somayeh Sadeghi Goghari; Sedigheh Yousefzadeh; Hassan Rakhshandeh; Salameh Dadghar; Seyed Reza Mazloom (Mashhad University of Medical Sciences, 2018)
Background & aim: Estrogen and androgen deficiency in menopause leads to poor vulvovaginal blood flow, vaginal dryness, and dyspareunia which can reduce the quality of life among the women. In this regard, this study investigated the impact of date palm pollen capsules on vaginal lubrication and dyspareunia in postmenopausal women. Methods: The present triple-blinded, placebo-controlled clinical trial was conducted on 60 ‌menopausal women aged 40-65 years, who referred to the health centers affiliated to the Mashhad University of Medical Sciences, Mashhad, Iran, in 2015. The subjects were randomly assigned to two groups of intervention and placebo (n=30), receiving date palm pollen and placebo capsules (350 mg, daily), respectively, for 35 days. The data were collected at two stages (at the baseline and after treatment) using the Female Sexual Function Index, a part of which evaluated vaginal lubrication and dyspareunia. Data analysis was performed in SPSS (version 16) using the independent t-test, Mann-Whitney U test, and ANCOVA. Results: There was a significant difference between the two groups after the intervention in terms of vaginal lubrication (P